Pengaruh Kebijakan Dividen Dan Kinerja Keuangan Terhadap Harga Saham Dimoderasi Oleh Ukuran Perusahaan: Studi Empiris Pada Perusahaan LQ45 Yang Terdaftar Di BEI Periode 2018-2022 - Muhammad, Aisya Amelia; Margie, Lyandra Aisyah (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2026)
In March 2020, all LQ45 stock indexes have experienced a significant decline. The decline in stock prices was influenced by unfavorable conditions such as Covid-19. Other factors that support the rise and fall of stock prices are supply and demand, dividend policy, financial performance, and company size. The purpose of this study is to analyze the relationship between dividend policy and financial performance on stock prices moderated by company size. In this study, secondary data was taken from annual reports from LQ45 index companies and download from the website www.idx.co.id. The method in determining the sample used purposive sampling. The method used is multiple linear regression test with the help of E-views 12 software. The results of this study indicate that dividend policy and financial performance simultaneously have a significant effect on stock prices, partially dividend policy does not have a significant effect on stock prices and financial performance has a significant effect on stock prices, while company size is able to moderate the effect of dividend policy and financial performance on stock prices.